Measuring the efficiency of sharia business units of Indonesian private banks: a data envelopment analysis approach - Ulkhaq, M. Mujiya (Journal of Islamic Economics Management and Business (JIEMB), 2022)
With the development of sharia banks, one of the effects is the existence of competition among sharia banks. This study analyses the efficiency of sharia business units of private banks in Indonesia. Understanding efficiency is essential because if banks perform consistently with total efficiency, the fewer inputs they use, the larger their output. Total earning assets measure the output, while the inputs used are total deposit and total operating costs. A data envelopment analysis with input-oriented and variable returns-to-scale is used to accomplish the objective. The result shows that three of the seven sharia business units under investigation are considered the most efficient. This indicates that the sharia business unit does not have to have the highest output value to be the most efficient one. It also must have low values of inputs.Keywords: data envelopment analysis; efficiency; Indonesian private bank; sharia business unit.